Pengaruh Kesadaran, Kualitas Pelayanan, Dan Pemeriksaan Pada Kepatuhan Wajib Pajak Bermotor Di Kabupaten Gianyar - Krismayanti, Ni Putu; Lely Aryani Merkusiwati, Ni Ketut (E-Jurnal Akuntansi; Vol 28 No 2 (2019), 2019)
The purpose of this research was to obtain empirical evidence from the influence of taxpayer awareness, tax service quality and tax audit on motor vehicle taxpayer compliance in Gianyar Regency. This research was conducted in Gianyar Regency. The population in this study were all Motor Vehicle taxpayers scattered in Gianyar Regency. The number of samples in this study were 100 respondents using the sampling method was accidental sampling. Data collection is done using a questionnaire. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis, it can be seen that, taxpayer awareness, tax service quality and tax audit have a significant positive effect on motor vehicle taxpayer compliance in Gianyar Regency. Keywords : Compliance, awareness, service quality, examination.